RESPONS TANAMAN BAYAM MERAH (Amaranthus sp.) TERHADAP PEMBERIAN PUPUK SERTA SIFAT FISIK DAN KIMIA TANAHNYA - Orinus Kogoya; Joko Purbopuspito; Jenny J. Rondonuwu (Universitas Sam Ratulangi, 2018)
ABSTRACT This study aims to determine the effect of compost, NPK and Urea fertilizer on the growth of Red Spinach (Amaranthus, sp.) Plants and the physical and chemical properties of the soil. which fertilizer is best for red spinach plants and for soil analysis is carried out at the Soil Physics Laboratory and Soil Chemistry and Soil Fertility, Faculty of Agriculture, Sam Ratulangi University, Manado. This research was conducted using the Completely Randomized Design Method (CRD), where R0 was the control, R1 chicken manure compost, R2 NPK, Urea R3, this research was carried out in 4 treatments and 3 to obtain 12 experimental plots / beds. The results of this study indicate that the land in the Manado City Pakowa Village has a sandy loam and clay texture which has a relatively fast permeability rate, and has a slightly acidic soil acidity to the availability of nutrients N, P, K and C-organic is relatively low. Kata Kunci : Bayam Merah, Pengaruh Pupuk, Fisik dan Kimia